Outcomes of myasthenia gravis patients admitted to the Intensive Care Unit: Experience from a tertiary care center in Saudi Arabia - Ahmed Attar; Hatoon Alshaikh; Ghadi Alharbi; Tala Aletani; Sara Alghamdi; Sarah Alzahrani; Osama Khojah; Rahma Alqthmi; Abdulrahman Althobaiti; Thamer Alaifan (PLoS ONE, 2025)
Background Myasthenia gravis is an autoimmune disorder that affects the neuromuscular junction resulting in muscle weakness and fatigue. The aim of this study was to investigate the indications for and frequency of intensive care unit admissions in people with myasthenia gravis in addition to exploring the clinical presentations and outcomes during their admission. Methods and Findings This retrospective study included all adult patients diagnosed with myasthenia gravis who were admitted to the intensive care unit in a six year period. Twenty-four patients with a diagnosis of myasthenia gravis were included in this study, with a total of 60 admissions. The median age at their first admission was 45 years with female predominance. Majority of the patients (87.5%) were acetylcholine antibody positive and 66.7% of patients had thymectomy. Myasthenic crisis was the most common reason for intensive care unit admission (63.3%). 80.5% of patients admitted with myasthenic crisis were treated with plasma exchange. During their admission, 45% of patients required mechanical ventilation. Complications during hospitalization were reported in 18.3% of patients, with mortality rate of 5% of all admissions. Conslusion People with myasthenia gravis are commonly admitted to the intensive care unit due to myasthenic crises, however, there were minimal complications reported and a low mortality rate.